1996
DOI: 10.1007/bf02353802
|View full text |Cite
|
Sign up to set email alerts
|

Postural orientation modifications in autism in response to ambient lenses

Abstract: Autistic children often display abnormal postures, head tilts, and other spatial management dysfunctions. Methods were introduced to measure spatial orientation in tasks in a group of fourteen autistic children in Montreal, Canada. Ambient lenses were found to improve posture, correct head tilts, and improve ball catching abilities. A model of spatial orientation is described and recommendations are made to incorporate ambient lenses in treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…John's balance and coordination was assessed with a ball catching task and a beam walking exercise. These tasks were designed to be similar to those previously employed by other researchers examining the effects of ambient lenses (Carmody et al, 2001;Kaplan et al, 1996;Kaplan et al, 1998). One of the three experimental conditions-control (no lenses), ambient lenses, placebo lenses-was conducted each school day, and each session consisted of 10 trials of each task.…”
Section: Measurement Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…John's balance and coordination was assessed with a ball catching task and a beam walking exercise. These tasks were designed to be similar to those previously employed by other researchers examining the effects of ambient lenses (Carmody et al, 2001;Kaplan et al, 1996;Kaplan et al, 1998). One of the three experimental conditions-control (no lenses), ambient lenses, placebo lenses-was conducted each school day, and each session consisted of 10 trials of each task.…”
Section: Measurement Design and Proceduresmentioning
confidence: 99%
“…The Kay and Vyse study was reported in a book chapter rather than a peer-reviewed publication, however. Two other studies published in the same peer-reviewed journal (Carmody et al, 2001;Kaplan, Carmody, & Gaydos, 1996), reported immediate improvements in performance on visual-motor tasks while participants wore the lenses. An additional study published in the same journal (Kaplan et al, 1998), reported no improvements on these tasks but did report improvements on the Aberrant Behavior Checklist (Aman, Singh, Stewart, & Field, 1985), which relies on reports of caregivers and yields a global score regarding problem behavior.…”
mentioning
confidence: 92%
“…The purpose of yoked prisms (sometimes also referred to as ‘conjugate’ prisms or ‘ambient lenses’, e.g. Kaplan et al. (1996); Kaplan and Carmody (1997)) is not therefore to address a vertical or horizontal imbalance between the eyes, but, in the words of Birnbaum (1993) (p.186), ‘ their effect is rather to create spatial change ’ (see below).…”
Section: Yoked Prisms For Near Binocular Disorders and For Producing mentioning
confidence: 99%
“…Potential sources of bias in previous studies include partially or entirely subjective assessment of posture and performance, or a lack of masking of participants or researchers. [9][10][11][12][13] Gizzi et al 10 used an objective method (moving platform posturography) to measure posture in healthy individuals without prisms, immediately on wearing 15-diopter (D) base right yoked prisms and after wearing the prisms for 1 hour. Statistically significant shifts in posture toward the prism base (right) were reported at both time points, but multiple comparisons were made with no mention of a correction factor for these.…”
mentioning
confidence: 99%